Efficient dynamic searchable encryption scheme for conjunctive queries based on bidirectional index - Ruizhong DU; Yuqing ZHANG; Mingyue LI (Tongxin xuebao)
To solve the problems of complicated operation, information leakage, and inflexible query method in the update process of existing dynamic searchable encryption scheme, an efficient dynamic searchable encryption scheme (named BPC-DSSE) for conjunctive query with forward and backward privacy was proposed.A bitmap index was used to construct a bidirectional index structure to simplify the dynamic update process, and the access pattern was hidden through symmetric encryption with homomorphic addition.At the same time, since the addition and deletion operations were completed by modulo addition, the leakage of the update process could be reduced by hiding the update type.Security analysis shows that the BPC-DSSE scheme achieves forward and Type-I- backward privacy.The simulation results show that the BPC-DSSE scheme has higher update and retrieval efficiency than other conjunctive query schemes.